Epidemiology and outcomes of primary sclerosing cholangitis with and without inflammatory bowel disease in an Australian cohort. (24th January 2017) - Liu, Ken; Wang, Ruoxi; Kariyawasam, Viraj; Wells, Mark; Strasser, Simone I.; McCaughan, Geoff; Corte, Crispin; Leong, Rupert W.
Abstract: Background & Aims: Epidemiological data on primary sclerosing cholangitis (PSC) outside the Northern hemisphere are limited. Similarly, the impact of inflammatory bowel disease (IBD) on PSC outcomes remains unclear. We aimed to study the epidemiology and outcomes of PSC patients with and without IBD in an Australian cohort. Methods: We retrospectively studied PSC patients attending two tertiary referral hospitals over 20 years. Diagnosis of PSC was made according to international guidelines by positive cholangiography and/or liver biopsy (for small duct PSC) with supporting clinical and laboratory evidence. Results: Of 208 PSC patients (61% male) were studied (2271patient‐years follow‐up). The median age of PSC diagnosis was similar for PSC‐IBD and PSC‐only patients (40 years vs 42 years, P = .35). All 33 deaths occurred in PSC‐IBD patients while there were no deaths in PSC‐only patients (21% vs 0%, P < .01). However, there were no significant differences in liver transplantation (PSC‐only 25% vs PSC‐IBD 31%, P = .45) and transplant‐free survival between PSC‐only and PSC‐IBD patients ( P = .43). On multivariate Cox regression, only elevated international normalized ratio (INR) was associated with a greater risk of death or liver transplant (HR 2.0, 95% CI 1.1‐3.6, P = .02). Development of gastrointestinal malignancy was higher in the PSC‐IBD group compared to PSC‐only group (22% vs 2%, P < .01). Conclusion: Australian PSC patients have similar characteristics compared to European and North American cohorts. IBD is a significant predictor of gastrointestinal malignancies. Deaths were more common in PSC‐IBD but overall transplant‐free survival remained similar in PSC‐IBD and PSC‐only groups. An elevated INR was an independent predictor of death or liver transplantation.